2015
DOI: 10.17795/ijpbs209
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory and Response Inhibition in Patients With Bipolar I Disorder During Euthymic Period

Abstract: Background:Several cognitive domains, including attention, memory, and executive functions are impaired in bipolar disorder.Objectives:This study aimed to investigate two executive functions (working memory and response inhibition) in patients with bipolar I disorder during remission of the symptoms.Patients and Methods:In this case-control design, 30 bipolar I patients (18 to 45 years old) were matched with 30 ones in the control group in terms of age, gender, and education. The patients were selected from Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Deficits in WM processing have been consistently reported in euthymic patients (MacQueen et al, 2005 ; Thompson et al, 2007 ; Daglas et al, 2015 ). Another study also observed that euthymic BD type I had worse performance on visuospatial tasks compared to healthy subjects (Farahmand et al, 2015 ). Although, there is no consensus in the literature, these findings suggest that lower performance in WM could result in the intensification of emotional valences.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Deficits in WM processing have been consistently reported in euthymic patients (MacQueen et al, 2005 ; Thompson et al, 2007 ; Daglas et al, 2015 ). Another study also observed that euthymic BD type I had worse performance on visuospatial tasks compared to healthy subjects (Farahmand et al, 2015 ). Although, there is no consensus in the literature, these findings suggest that lower performance in WM could result in the intensification of emotional valences.…”
Section: Discussionmentioning
confidence: 89%
“…Updating deficits of visuospatial information were found in depressive BD patients assessed by n-back tasks (Deckersbach et al, 2008 ; Pomarol-Clotet et al, 2014 ) and in mania phases (Pomarol-Clotet et al, 2014 ). Despite WM alterations have been reported during mood episodes of BD, it is suggested that deficits in WM persist during remission of symptoms (MacQueen et al, 2005 ; Thompson et al, 2007 ; Daglas et al, 2015 ; Farahmand et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to voluntarily inhibit unnecessary actions is an important aspect in psychiatric disorders. Indeed, deficits in action inhibition were identified in different psychopathological conditions, including schizophrenia (Tsujii et al, 2018;Yang et al, 2020;Yu et al, 2019), bipolar disorder (Farahmand et al, 2015;Hidiroğlu et al, 2015), attention deficit hyperactivity disorder -ADHD (Janssen et al, 2015;Senderecka et al, 2012), Parkinson's disease (Di Caprio et al, 2020;Mirabella et al, 2017), substance use disorders (Smith & Mattick, 2013;Wang et al, 2018) and obsessive-compulsive disorder (De Wit et al, 2012;McLaughlin et al, 2016;Sohn et al, 2014; for a meta-analysis see Lipszyc & Schachar, 2010). However, there are also studies that report contradictory results or that ascribed the poor inhibitory control observed in psychiatric patients to more generalized attentional and/or cognitive problems (Alderson et al, 2007;Elton et al, 2014;Kalanthroff et al, 2017;Lyche et al, 2010;Matzke et al, 2017;Weigard et al, 2019).…”
Section: Emotional Stimuli and Response Inhibition In Psychiatric Pop...mentioning
confidence: 99%
“…Bipolar disorder (BD) is a chronic and severe psychiatric illness characterized by an early onset and a cyclic alternation of manic and depressive episodes, whereas major depressive disorder (MDD) patients experience long periods of decreased mood, self‐esteem, energy, and interests. Beside clinical symptoms, both disorders are characterized by impaired cognitive performances involving several cognitive domains: attention, working memory, verbal fluency, attention/speed of information processing, and executive functions . Moreover, even if cognitive deficits are more severe during active phases (depressive and/or manic episodes), they are still also present during euthymia, probably representing a core feature of these pathologies .…”
mentioning
confidence: 99%